Language and Authority in Scientific Articles on the Indone-sian Language: A Conceptual Review - Hasnah Faizah; Nazhifa Fadila; El Firdausia Yahfis (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Scientific articles not only function as a medium for conveying information but also as a representation of the author’s academic credibility and intellectual authority within the scientific community. In academic writing, language plays a crucial role in shaping the author’s identity, reliability, and scholarly position. This research aims to conceptually examine the relationship between linguistic choices and the construction of authority in Indonesian-language scientific articles. The study employs a library research method with a critical discourse analysis approach toward various references related to functional linguistics, discourse studies, and ethics in academic writing. The findings indicate that academic authority is constructed through several linguistic aspects, including lexical precision, grammatical objectivity, cohesion and coherence of ideas, as well as a careful epistemological attitude that remains open to alternative interpretations and scientific dialogue. In addition, the use of formal, systematic, and evidence-based language contributes significantly to strengthening the legitimacy of scientific arguments. Within this framework, language is not merely a communication tool used to present ideas, but also an instrument for legitimizing knowledge and reinforcing the author’s credibility, reliability, and authority in academic discourse. Therefore, mastery of academic language becomes an essential component in producing quality scientific articles.